KAJIAN PENGARUH KONDISI DAERAH RESAPAN AIR PADA POLA PEMANFAATAN RUANG DI SUB DAS JLANTAH-WALIKUN PADA WILAYAH DAS BENGAWAN SOLO HULU - Rahardhiansyah Setyawan Alfandhani; Dyah Rahmawati Hizbaron; Margaretha Widyastuti (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Jlantah-Walikun subwatershed has a very significant development activity infrastructure which certainly has influenced the condition water catchment area. This study was written to examine the effect of water catchment conditions on space utilization patterns. The method overlay used to review criteria water catchment area conditions based on the number of values each supporting variable, the influence water catchment conditions with space utilization patterns by doing with overlay processing results and compiling water catchment area directives. The results of water catchment condition research obtained at the Jlantah-Walikun subwatershed were dominated by good, natural normal, rather critical condition criteria, starting critically and critical area. The effect of catchment condition with the pattern of utilization of space there are three results: influential, very influential, and no effect and direction water catchment area there are three criteria, appropriate, quite appropriate and not appropriate.